Sphingomyelin SM(d18:1/18:0) is Significantly Enhanced in Cerebrospinal Fluid Samples Dichotomized by Pathological Amyloid-β(42), Tau, and Phospho-Tau-181 Levels - Koal, Therese (J Alzheimers Dis, 2015)
Alzheimer’s disease (AD) is a severe and chronic neurodegenerative disorder of the brain. The laboratory diagnosis is limited to the analysis of three biomarkers in cerebrospinal fluid (CSF): amyloid-β(42) (Aβ(42)), total tau, and phospho-tau-181 (P-tau-181). However, there is a need to find more biomarkers in CSF that can improve the sensitivity and specificity. The aim of the present study was to analyze endogenous small metabolites (metabolome) in the CSF, which may provide potentially new insights into biochemical processes involved in AD. One hundred CSF samples were dichotomized by normal (n = 50) and pathological decreased Aβ(42) and increased tau and P-tau-181 levels (n = 50; correlating to an AD-like pathology). These CSF samples were analyzed using the AbsoluteIDQ(®) p180 Kit (BIOCRATES Life Sciences), which included 40 acylcarnitines, 21 amino acids, 19 biogenic amines, 15 sphingolipids, and 90 glycerophospholipids. Our data show that two sphingomyelins (SM (d18:1/18:0) and SM (d18:1/18:1)), 5 glycerophospholipids (PC aa C32:0, PC aa C34:1, PC aa C36:1, PC aa C38:4 and PC aa C38:6), and 1 acylcarnitine (C3-DC-M/C5-OH) were significantly altered in the CSF with pathological “AD-like pathology”. Sphingomyelin SM (d18:1/18:0) proved to be a specific (76%) and sensitive (66%) biomarker with a defined cut-off of 546 nM. Correct diagnoses for 21 out of 32 unknown samples could be achieved using this SM (d18:1/18:0) cut-off value. In conclusion, the sphingolipid SM (d18:1/18:0) is significantly increased in CSF of patients displaying pathological levels of Aβ(42), tau, and P-tau-181.